Manortor as a Solidarity and Identity Building Media of Mandailing Ethnic Group in Rokan Hulu, Riau Province - Novita, Elmi; Soewarlan, Santosa; Sukerna, Nyoman (Harmonia: Journal of Arts Research and Education, 2022)
This study aimed to explore manortors as a medium for building solidarity and identity for the Mandailing community in Rokan Hulu Regency, Riau Province. The research method was carried out through observation of manortor performances in Menaming, Bangun Purba, and Khaiti Villages as Mandailing ethnic dominions in Rokan Hulu. The observation focused on the movement aspect of the manortor. In-depth interviews were conducted to reinforce the data obtained through the observation of the manortor and to explore how aspects of the movement in the manortor build solidarity and identity. The results showed that manortor is a dance that embodies kinship relationships with dalihan na tolu. The form of movement, standing position, and order of performance should be in line with the norms of kinship. The group members dance together with movements representing kinship relationships and strengthening kinship relationships, building solidarity and a strong self-identity.English translation.